1992
DOI: 10.1007/bf00226705
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic relationships in response to NaCl at different developmental stages in alfalfa

Abstract: The perennial forage alfalfa (Medicago sativa L.) may be affected by salinity at all stages of development. Selection for increased seed germination or seedling growth in saline environments has not resulted in improved forage yield under salt stress. The purpose of this study was to determine genetic and phenotypic relationships between plant performance in the presence of NaCl at three developmental stages in alfalfa. Understanding these relationships may improve the efficiency of breeding programs aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 23 publications
8
60
0
Order By: Relevance
“…The results obtained when the responses to salt stress during germination and vegetative growth were compared suggested that the genetic controls underlying NaCl tolerance in Arabidopsis are different, because the most tolerant accessions to NaCl at germination were the most sensitive to this salt during vegetative growth. Similar results have been previously reported for other plant species such as soybean (Glycine max; Abel and Mackenzie, 1963), wheat (Triticum aestivum; Kumar et al, 1983), alfalfa (Medicago sativa; Johnson et al, 1992), barley (Mano and Takeda, 1997), and tomato (Foolad, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…The results obtained when the responses to salt stress during germination and vegetative growth were compared suggested that the genetic controls underlying NaCl tolerance in Arabidopsis are different, because the most tolerant accessions to NaCl at germination were the most sensitive to this salt during vegetative growth. Similar results have been previously reported for other plant species such as soybean (Glycine max; Abel and Mackenzie, 1963), wheat (Triticum aestivum; Kumar et al, 1983), alfalfa (Medicago sativa; Johnson et al, 1992), barley (Mano and Takeda, 1997), and tomato (Foolad, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…The tomato response to salt stress is differently regulated in different development stages (Costa et al 1990;Saranga et al 1992;Foolad 2004). This has also been reported in other crop species (Greenway and Munns 1980;Shannon 1985;Maas 1986;Lauchli and Epstein 1990;Johnson et al 1992;. During flowering and fruit setting, tomato plants are able to withstand NaCl concentrations which are sufficient to kill them in the seedling stage (Elshourbagy and Ahmed 1975).…”
Section: Introductionsupporting
confidence: 66%
“…Na + and Cl − , which may lower their water absorption potential. Various reports indicate that salt tolerance is development stage specific processes because one developmental stage may be drastically affected while other exhibit tolerance to salts [12]. The results regarding the seedling height and seedlings fresh and dry weight confirmed these findings of Ahmad and Khan [13].…”
Section: Effect Of Salt Stress On Growth Attributessupporting
confidence: 81%